POP1 might be recruiting its type‐Ia interface for NLRP3‐mediated PYD‐PYD interaction: Insights from MD simulation. Issue 9 (3rd April 2017) - Maharana, Jitendra; Vats, Ashutosh; Gautam, Santwana; Nayak, Bibhu Prasad; Kumar, Sushil; Sendha, Jasobanta; De, Sachinandan
Abstract: Inflammasomes are multiprotein caspase‐activating complexes that enhance the maturation and release of proinflammatory cytokines (IL‐1β and IL‐18) in response to the invading pathogen and/or host‐derived cellular stress. These are assembled by the sensory proteins (viz NLRC4, NLRP1, NLRP3, and AIM‐2), adaptor protein (ASC), and effector molecule procaspase‐1. In NLRP3‐mediated inflammasome activation, ASC acts as a mediator between NLRP3 and procaspase‐1 for the transmission of signals. A series of homotypic protein‐protein interactions (NLRP3 PYD :ASC PYD and ASC CARD :CASP1 CARD ) propagates the downstream signaling for the production of proinflammatory cytokines. Pyrin‐only protein 1 (POP1) is known to act as the regulator of inflammasome. It modulates the ASC‐mediated inflammasome assembly by interacting with pyrin domain (PYD) of ASC. However, despite similar electrostatic surface potential, the interaction of POP1 with NLRP3 PYD is obscured till date. Herein, to explore the possible PYD‐PYD interactions between NLRP3 PYD and POP1, a combined approach of protein‐protein docking and molecular dynamics simulation was adapted. The current study revealed that POP1's type‐Ia interface and type‐Ib interface of NLRP3 PYD might be crucial for 1:1 PYD‐PYD interaction. In addition to type‐I mode of interaction, we also observed type‐II and type‐III interaction modes in two different dynamically stable heterotrimeric complexes (POP1‐NLRP3‐NLRP3 and POP1‐NLRP3‐POP1). The inter‐residual/atomic distance calculation exposed several critical residues that possibly govern the said interaction, which need further investigation. Overall, the findings of this study will shed new light on hitherto concealed molecular mechanisms underlying NLRP3‐mediated inflammasome, which will have strong future therapeutic implications. Abstract : In NLRP3‐mediated inflammasome, POP1 shows regulatory activity interacting with ASC. Despite similar electrostatic surface potentials, the interaction of POP1 with NLRP3 is obscured till date. Using structural bioinformatics approaches, we explored that POP1's type Ia interface might be crucial for POP1‐NLRP3 PYD‐PYD interaction.